Analytic integrability of quasi-homogeneous systems via the Yoshida method. (May 2021) - García, Belén; Llibre, Jaume; Lombardero, Antón; Pérez del Río, Jesús S.
Abstract: The objective of this paper is twofold. First we do a survey on what we call the Yoshida method for studying the analytic first integrals of the quasi-homogeneous polynomial differential systems. After, we apply the Yoshida method for studying the analytic first integrals of all the quasi-homogeneous polynomial differential systems in R 3 of degree 2.